Eckhart's Systematics: Christ the God‐Human Ground. (23rd June 2022) - Vale, Matthew
Abstract: Meister Eckhart's notion of the ground ( grunt ) is a full‐bore speculative Christological protology‐ cum ‐eschatology. This essay reconstructs a systematic account of it unavailable elsewhere, and proposes it to contemporary systematics. The ground is the higher aeon of eternity, where God ceaselessly and primordially creates, the Son becomes incarnate, and the eternal incarnation joins creatures to the Father's primal unity. In the ground, the creation is supratemporally always being protologically brought forth and eschatologically consummated. This bringing forth and consummating is none other than the eternal incarnation: the primordial birthing of all creatures as the "one Christ" ( éin Kristus ), the universal God‐human ( mensche‐got ). The God‐human unity of the ground, in fact, just is Christ: the lived identity of divine and human natures as a single personal esse . For Eckhart, these claims are not eccentric. They follow from basic Christian premises. If God is fully actual, then all God's proper acts are atemporally fully actual. There is, then, a higher aeon where the creation that is the terminus of God's fully actual act is primordially always being consummated. God's creating, becoming human, and joining creatures to himself is co‐primordial with God being God: it belongs to God's proper life. This is the unity of the ground, and it is, in fact, the unity of the primordial incarnation.